Management of Indigenous Knowledge and Quality Education Delivery in Public Senior Secondary Schools in Rivers State, Nigeria - Catherine, Ukala Chinyere (Archives of Business Research, 2025)
The study investigated management of indigenous knowledge and quality education delivery in senior secondary schools in Rivers State, Nigeria. Three objectives, three research questions and three hypotheses guided the study. The study adopted correlational research design. The population for this study consisted of the 313 principals in 313 public senior secondary schools in Rivers State. The sample size used for the study was 313 respondents using census sampling technique. The instruments for data collection are two self-structured questionnaires titled “Management of Indigenous Knowledge Questionnaire and Quality Education Delivery Questionnaire with 30 items. The reliability coefficient of management of indigenous knowledge was .86 and quality education delivery was .87 while utilization of indigenous knowledge was .83 and strategies to improve indigenous knowledge was .89 using Cronbach method. The research questions were answered using simple regression statistics, while t-test was used to test the hypotheses at 0.05 level of significance. The findings among others showed that management of indigenous knowledge contributed to quality education delivery by 21.8% while the hypothesis showed that management of indigenous knowledge significantly contributed to quality education delivery in senior secondary schools in Rivers State.